Differential effects of tau expression on seizures and epileptogenesis in a mouse model of temporal lobe epilepsy - Moseley, Madeleine C.; Cloyd, Ryan A.; Burns, Liam; Roberts, Rafael; Kang, Young-Jin; Lee, Sang-Hun; Smith, Bret N. (Frontiers in Systems Neuroscience, 2025)
Studies of the microtubule-associated protein, tau suggest its promise as a potential target for epilepsy disease modification, but mechanisms underlying tau’s effects on seizures are not well-defined. Acquired temporal lobe epilepsy (TLE) is the most prevalent form of focal epilepsy, yet the impact of tau expression on the process of TLE development is unexplored. We investigated tau’s role in the epileptogenesis of acquired TLE using the intrahippocampal kainate (IHK) model in mice lacking tau expression (i.e., tau−/− mice). We examined epileptiform activity during status epilepticus (SE) after IHK injection and assessed the subsequent development of spontaneous recurrent seizures (SRS) using video and video-electroencephalography (v-EEG). Results demonstrate that the lack of tau expression did not prevent evoked seizures or the development of TLE but reduced the number of convulsive seizures during SE and the severity of spontaneous seizures after TLE developed by suppressing epileptiform electrographic activity of convulsive seizures, which has not been shown in the context of an acquired TLE model. We assayed excitatory and inhibitory synaptic properties of dentate granule cells (DGCs) in the dorsal hippocampus using whole-cell patch clamp electrophysiology once TLE developed. Our results show that DGCs in tau−/− mice receive significantly fewer spontaneous inhibitory synaptic current events than in wildtype controls and, after tau−/− mice develop TLE, DGCs develop increased contralateral inhibitory input. The modified inhibitory synaptic neuroplasticity associated with acquired TLE development, which is consistent with altered EEG spectra during convulsive seizures, may contribute to modified spontaneous seizure expression. Deletion of tau expression therefore modifies seizure expression, potentially via mechanisms involving inhibitory synaptic circuits in the dentate gyrus but does not prevent epileptogenesis in a murine model of acquired TLE.